Factors that Lead to Adoption and Use of Online Bank Account Opening through e-KYC using UTAUT and its Extensions - Elinzano, Gerand Boy O.; Ching, Michelle Renee D. (RSF Conference Series: Engineering and Technology, 2022)
Financial Inclusion has been determined as one of the factors affecting national development. Bank account opening provides opportunity to more banking services and as such central banks have been supporting the use of Electronic-Know-Your-Customer (e-KYC) even before COVID-19 pandemic. While the benefits of e-KYC for the banks and its customers are clear, the widespread use of such process for account opening is still in its early adoption stage. This research employed a quantitative method by adopting the Unified Theory of Acceptance and Use of Technology as as theoretical foundation and extension constructs and determined the factors affecting the use and adoption of e-KYC for online bank account opening. As a result, facilitating conditions and perceived security were found to be significant factors affecting the intension to use e-KYC. Through this research, it was able to validate the use of the research model in studying e-KYC adoption and provided management key areas leading to e-KYC use that they may focus on.